THE INFLUENCE OF CELEBRITY ENDORSEMENT AND INSTAGRAM ONLINE PROMOTION TOWARDS ONLINE PURCHASING DECISIONS OF WARDAH COSMETIC PRODUCTS IN MANADO CITY - Missi Rantung; Willem J. F. A. Tumbuan; Regina T. Saerang (Universitas Sam Ratulangi, 2024)
Wardah is one of the leading cosmetic brands in Indonesia, offering skin care products and brands that are halal certified and suitable for the Indonesian market. This research aims to analyze the influence of celebrity endorsements and online Instagram promotions on online purchasing decisions for Wardah cosmetic products in the city of Manado. Researchers used people who used Wardah products as objects, researchers used quantitative methods by testing variable relationships, the number of samples used in this research was 100 respondents aged 19-40 years. The sampling method used was purposive sampling, with a questionnaire as a data collection tool. The research results show that celebrity endorsements have a positive influence on purchasing decisions. Keywords: celebrity endorsement, online promotion, online purchasing decisions